Effects of Combination of Long - Term Ginger Consumption and Resistance Training on Lipid Peroxidation and Insulin Resistance in Obese Men - S Atashak; MA Azarbayjani; M Piri; A Jafari (Institue of Medicinal Plants, ACECR, 2012)
Objectives: Therefore, the present study investigated the effects of long-term ginger consumption and progressive resistance training on lipid per oxidation and insulin resistance in obese men. Methods: In a randomized double-blind design, 32 obese men (BMI≥ 30) were assigned in to one of four groups: a Placebo (PL,n=8), Ginger group, that consumed 1 gr ginger/d for 10 wk (GI,n=8), resistance training plus Placebo (PLRT,n=8), and 1gr ginger plus resistance exercise (GIRT, n=8). Progressive resistance training was performed three days per week for 10 weeks and included 8 exercises. At baseline and after 10 weeks venous blood samples were obtained from the antecubital vein, and Malondialdehyde (MDA) as an indicator of lipid peroxidation, pectrophotometrically were assayed by measurement of TBARS assay. Moreover, insulin resistance was determined using a homeostasis model assessment (HOMA-IR). Two-way ANOVA were used in the statistical analysis. Results: After 10 weeks of intervention, we observed a significant decrease for MDA concentration in all groups exception Placebo group (P<0.05). Moreover, significant decreases in the mean values of insulin resistance were observed in CIRT and PLRT groups (P<0.05). While it remained unchanged in GI and PL groups (p>0.05) Conclusion: Therefore, according to this results it can be said, that, long term ginger consumption and resistance training has been an effective therapeutic devise to favorable changes in lipid peroxidation and insulin resistance in obese men.